2014
DOI: 10.1111/sjtg.12086
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of crop diversity in the regions of Bangladesh (1990–2008)

Abstract: The paper measures the level of crop diversity and identifies factors influencing diversification using a panel data of 17 regions of Bangladesh covering a 19 year period (1990–2008). Results revealed the trends that agricultural areas allocated to high‐yielding variety rice, spices and vegetables has increased, while areas cultivating traditional rice, minor cereals, oilseeds, pulses, jute and sugarcane has declined at variable rates across regions with significant differences. The level of crop diversity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…Furthermore, an analysis in Argentina showed that diversified farming increased the mean return on capital with a lower coefficient of variation (Pacín and Oesterheld, 2014). Hence, the multiple crop farming may be a means of enhancing revenue (Ali et al, 2004;Winters et al, 2006;Pacín and Oesterheld, 2014;Rahman and Kazal, 2015). However, the diversification took place slowly due to agricultural subsidies concentrated on a certain crop such as rice in India (Bhattacharyya, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, an analysis in Argentina showed that diversified farming increased the mean return on capital with a lower coefficient of variation (Pacín and Oesterheld, 2014). Hence, the multiple crop farming may be a means of enhancing revenue (Ali et al, 2004;Winters et al, 2006;Pacín and Oesterheld, 2014;Rahman and Kazal, 2015). However, the diversification took place slowly due to agricultural subsidies concentrated on a certain crop such as rice in India (Bhattacharyya, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Farmers who have access to irrigation are 5.3% more likely to grow more crops. Bazaz and Haq (2013), Rahman andKazal, 2015, Kumar andGupta (2015), Abro (2012), Mesfin et al (2011) andLonnie et al (1989) also found a positive relationship between irrigation and enterprise diversification.…”
Section: International Journal Of Regional Developmentmentioning
confidence: 95%
“…The significantly lower crop diversity of nonfarming households than that of other three household groups (p<0.05) indicates that nonfarming households tend to specialize on specific crops and denotes a dependent relationship between labour availability on farm and crop diversity in smallholder households (Rahman & Kazal, ). In Hu Village, nonfarming households often tend to focus on less labour‐intensive crops (i.e., citrus, cash trees) and receive significantly less agricultural subsidiaries than the other three types of households (p=0.00), and this finding again suggests that nonfarming households are more likely to move out of agriculture.…”
Section: Resultsmentioning
confidence: 99%